PENGATURAN PAJAK DAERAH DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA DAN KOTA YOGYAKARTA. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The enactment of Act Nr. 28 of 2009 on Local Taxes and Local Levies would allegedly pose some juridical impact on local tax collection at the provincial and districtlcities throughout Indonesia. The juridical impact would at least occur to local regulations governing local taxes, Regional Government Revenue and Expenditure (APED), and the oversight of local regulation by the provincial and district/ city governments. This research is a normative-empirical research, which aims to analyse changes of local taxes law in Act Nr. 28 of 2009. This study offers an insight of the impact of this Act on local tax collection in the special province of Yogyakarta.